Differential Expression of Metabolism-Related Genes in Plateau Pika (Ochotona curzoniae) at Different Altitudes on the Qinghai–Tibet Plateau - Zhu, Hongjuan; Zhong, Liang; Li, Jing; Wang, Suqin; Qu, Jiapeng (Frontiers in Genetics, 2022)
According to life history theory, animals living in extreme environments have evolved specific behavioral and physiological strategies for survival. However, the genetic mechanisms underpinning these strategies are unclear. As the highest geographical unit on Earth, the Qinghai–Tibet Plateau is characterized by an extreme environment and climate. During long-term evolutionary processes, animals that inhabit the plateau have evolved specialized morphological and physiological traits. The plateau pika (Ochotona curzoniae), one of the native small mammals that evolved on the Qinghai–Tibet Plateau, has adapted well to this cold and hypoxic environment. To explore the genetic mechanisms underlying the physiological adaptations of plateau pika to extremely cold ambient temperatures, we measured the differences in resting metabolic rate (RMR) and metabolism-related gene expression in individuals inhabiting three distinct altitudes (i.e., 3321, 3663, and 4194 m). Results showed that the body mass and RMR of plateau pika at high- and medium-altitudes were significantly higher than those at the low-altitude. The expression levels of peroxisome proliferator-activated receptor α (pparα), peroxisome proliferator-activated receptor-γ coactivator-1α (pgc-1α), and the PR domain-containing 16 (PRDM16) in white (WAT) and brown (BAT) adipose tissues of plateau pika from high- and medium-altitudes were significantly higher than in pika from the low-altitude region. The enhanced expression levels of pgc-1α and pparα genes in the WAT of pika at high-altitude showed that WAT underwent “browning” and increased thermogenic properties. An increase in the expression of uncoupling protein 1 (UCP1) in the BAT of pika at high altitude indicated that BAT increased their thermogenic properties. The gene expression levels of pparα and pgc-1α in skeletal muscles were significantly higher in high-altitude pika. Simultaneously, the expression of the sarcolipin (SLN) gene in skeletal muscles significantly increased in high-altitude pika. Our results suggest that plateau pika adapted to an extremely cold environment via browning WAT, thereby activating BAT and enhancing SLN expression to increase non-shivering thermogenesis. This study demonstrates that plateau pika can increase thermogenic gene expression and energy metabolism to adapt to the extreme environments on the plateau.